1993
DOI: 10.1143/jjap.32.l687
|View full text |Cite
|
Sign up to set email alerts
|

Heteroepitaxial Growth of c-Axis-Oriented BaTiO3 Thin Films with an Atomically Smooth Surface

Abstract: C-axis-oriented barium titanate (BaTiO3) epitaxial films with an atomically smooth surface have been fabricated on SrTiO3{100} substrates using the pulsed laser deposition technique. The crystal structure and epitaxial orientation of the films have been analyzed by means of 2θ/θ X-ray diffractometry and 4-circle X-ray diffractometry. The highly oriented and epitaxial crystallinity is also shown by means of Rutherford backscattering spectrometry which gave a χmin of 1.7%. The atomically smooth surface comparabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Scarfone et al 11 found min ϭ20% in 70 nm thick BaTiO 3 films on MgO. Values as low as min ϭ1.7% have only been observed for BaTiO 3 on the structurally similar SrTiO 3 substrates by Gong et al 12 In good agreement with this reference, we have observed min values around 2% for BaTiO 3 films deposited on SrTiO 3 . The deposition parameters for films on SrTiO 3 were the same as those on MgO.…”
Section: A Structural Characterizationsupporting
confidence: 90%
“…Scarfone et al 11 found min ϭ20% in 70 nm thick BaTiO 3 films on MgO. Values as low as min ϭ1.7% have only been observed for BaTiO 3 on the structurally similar SrTiO 3 substrates by Gong et al 12 In good agreement with this reference, we have observed min values around 2% for BaTiO 3 films deposited on SrTiO 3 . The deposition parameters for films on SrTiO 3 were the same as those on MgO.…”
Section: A Structural Characterizationsupporting
confidence: 90%
“…Structure studies of bulk BaTiO 3 and SrTiO 3 started some 70 years ago [8][9][10], and thin film growth by pulsed laser deposition (PLD) was realized more than 20 years ago [11][12][13]. In spite of this long tradition of the study of these prototypical perovskite materials, many fundamental question are still open, especially for thin films in the nm thickness range.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17] This technique is distinguished by a short pulse duration, a short wavelength, and a huge energy flux of the laser beam used for PLD. The deposition process is accomplished by sitting on the substrate of a plume of ionized and ejected material which is produced by high-intensity laser irradiation of a solid target.…”
Section: Introductionmentioning
confidence: 99%